Futurescapes: evidence expectations in the USA for comparative effectiveness research for drugs in 2020. (August 2015) - Messner, Donna A; Mohr, Penny; Towse, Adrian
Aim: Explore key factors influencing future expectations for the production of evidence from comparative effectiveness research for drugs in the USA in 2020 and construct three plausible future scenarios.Materials & methods: Semistructured key informant interviews and three rounds of modified Delphi with systematic scenario-building methods.Results & conclusion: Most influential key factors were: health delivery system integration; electronic health record development; exploitation of very large databases and mixed data sources; and proactive patient engagement in research. The scenario deemed most likely entailed uneven development of large integrated health systems with pockets of increased provider risk for patient care, enhanced data collection systems, changing incentives to do comparative effectiveness research and new opportunities for evidence generation partnerships.